1998
DOI: 10.1021/bi981876+
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Transthyretin Acid Denaturation Pathways by Analytical Ultracentrifugation:  Implications for Wild-Type, V30M, and L55P Amyloid Fibril Formation

Abstract: Analytical ultracentrifugation methods were utilized to further characterize the acid denaturation pathways of wild-type, V30M, and L55P transthyretin (TTR) that generate intermediates leading to amyloid fibril formation and possibly the diseases senile systemic amyloidosis and familial amyloid polyneuropathy. Equilibrium and velocity methods were employed herein to characterize the TTR quaternary structural requirements for amyloid fibril formation. From neutral to slightly acidic conditions (pH 7.5-5.1), wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
231
1
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 202 publications
(250 citation statements)
references
References 50 publications
16
231
1
2
Order By: Relevance
“…Consistent with this, L55P TTR is markedly less stable to acid-induced tetramer dissociation and amyloid formation than V30M TTR, which is in turn less stable than wild type TTR. 11,[19][20][21] Thus, for these three variants, the ages of onset of TTR amyloid diseases correlate directly with the acid stabilities of the TTR tetramers involved.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Consistent with this, L55P TTR is markedly less stable to acid-induced tetramer dissociation and amyloid formation than V30M TTR, which is in turn less stable than wild type TTR. 11,[19][20][21] Thus, for these three variants, the ages of onset of TTR amyloid diseases correlate directly with the acid stabilities of the TTR tetramers involved.…”
Section: Introductionmentioning
confidence: 97%
“…7 Under acidic conditions, like those found in cellular organelles such as the lysosome, TTR dissociates to an alternatively folded, monomeric intermediate that self-assembles into amyloid fibrils. [8][9][10][11][12] The deposition of wild type TTR amyloid has been implicated to cause the disease senile systemic amyloidosis (SSA), whereas the deposition mutant TTR amyloid has been implicated to cause the diseases familial amyloid cardiomyopathy (FAC) and familial amyloid polyneuropathy (FAP); over 80 variants of TTR have been associated with FAC and FAP. 13,14 SSA involves the deposition of amyloid in the heart, with symptoms typically appearing around ages 70 to 80.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the conditions that promote the accumulation of amyloidogenic intermediates, as well as their underlying common structural features, should provide further information about amyloidogenesis in general. Recent biophysical studies on TTR have identified in vitro conditions that stimulate amyloid formation 9,10,20 ( Fig. 1).…”
mentioning
confidence: 99%
“…However, over the pH range of 5.0-3.9, TTR dissociates to a monomer that exhibits an altered but defined tertiary structure, as probed by fluorescence and far and near UV circular dichroism. The extent of amyloidogenesis correlates with the concentration of amyloidogenic monomer, which is maximal at pH 4.4 9,10 . Upon further acidification (< pH 3.9), the structurally defined monomers adopt alternative conformations analogous to a molten globule-like aciddenatured state (A-state), which forms low molecular weight A-state aggregates but not amyloid fibrils 21 .…”
mentioning
confidence: 99%
See 1 more Smart Citation